At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To determine the exact value(s) for which the rational expression [tex]\( f(x) = \frac{-11x + 1}{-30x^2 - 25x + 5} \)[/tex] is undefined, we need to identify the values of [tex]\( x \)[/tex] that make the denominator zero because division by zero is undefined in mathematics.
Let's set the denominator equal to zero and solve for [tex]\( x \)[/tex]:
[tex]\[ -30x^2 - 25x + 5 = 0 \][/tex]
This is a quadratic equation in the standard form [tex]\( ax^2 + bx + c = 0 \)[/tex], where [tex]\( a = -30 \)[/tex], [tex]\( b = -25 \)[/tex], and [tex]\( c = 5 \)[/tex]. To find the roots of this quadratic equation, we can use the quadratic formula:
[tex]\[ x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{2a} \][/tex]
First, we calculate the discriminant [tex]\( \Delta \)[/tex]:
[tex]\[ \Delta = b^2 - 4ac = (-25)^2 - 4(-30)(5) \][/tex]
[tex]\[ \Delta = 625 + 600 \][/tex]
[tex]\[ \Delta = 1225 \][/tex]
Since the discriminant is positive, we will have two distinct real roots. We proceed by substituting the values into the quadratic formula:
[tex]\[ x = \frac{{-(-25) \pm \sqrt{1225}}}{2(-30)} \][/tex]
[tex]\[ x = \frac{{25 \pm 35}}{-60} \][/tex]
Now, let's find the two roots:
1. For the [tex]\( + \)[/tex] case:
[tex]\[ x = \frac{{25 + 35}}{-60} = \frac{60}{-60} = -1 \][/tex]
2. For the [tex]\( - \)[/tex] case:
[tex]\[ x = \frac{{25 - 35}}{-60} = \frac{-10}{-60} = \frac{1}{6} \][/tex]
Thus, the values of [tex]\( x \)[/tex] that make the denominator zero and the rational expression [tex]\( f(x) \)[/tex] undefined are:
[tex]\[ x = -1, \frac{1}{6} \][/tex]
Therefore, the rational expression [tex]\( f(x) = \frac{-11x + 1}{-30x^2 - 25x + 5} \)[/tex] is undefined for [tex]\( x = -1 \)[/tex] and [tex]\( x = \frac{1}{6} \)[/tex].
Providing the answer in the required format,
[tex]\[ x = -1, \frac{1}{6} \][/tex]
Let's set the denominator equal to zero and solve for [tex]\( x \)[/tex]:
[tex]\[ -30x^2 - 25x + 5 = 0 \][/tex]
This is a quadratic equation in the standard form [tex]\( ax^2 + bx + c = 0 \)[/tex], where [tex]\( a = -30 \)[/tex], [tex]\( b = -25 \)[/tex], and [tex]\( c = 5 \)[/tex]. To find the roots of this quadratic equation, we can use the quadratic formula:
[tex]\[ x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{2a} \][/tex]
First, we calculate the discriminant [tex]\( \Delta \)[/tex]:
[tex]\[ \Delta = b^2 - 4ac = (-25)^2 - 4(-30)(5) \][/tex]
[tex]\[ \Delta = 625 + 600 \][/tex]
[tex]\[ \Delta = 1225 \][/tex]
Since the discriminant is positive, we will have two distinct real roots. We proceed by substituting the values into the quadratic formula:
[tex]\[ x = \frac{{-(-25) \pm \sqrt{1225}}}{2(-30)} \][/tex]
[tex]\[ x = \frac{{25 \pm 35}}{-60} \][/tex]
Now, let's find the two roots:
1. For the [tex]\( + \)[/tex] case:
[tex]\[ x = \frac{{25 + 35}}{-60} = \frac{60}{-60} = -1 \][/tex]
2. For the [tex]\( - \)[/tex] case:
[tex]\[ x = \frac{{25 - 35}}{-60} = \frac{-10}{-60} = \frac{1}{6} \][/tex]
Thus, the values of [tex]\( x \)[/tex] that make the denominator zero and the rational expression [tex]\( f(x) \)[/tex] undefined are:
[tex]\[ x = -1, \frac{1}{6} \][/tex]
Therefore, the rational expression [tex]\( f(x) = \frac{-11x + 1}{-30x^2 - 25x + 5} \)[/tex] is undefined for [tex]\( x = -1 \)[/tex] and [tex]\( x = \frac{1}{6} \)[/tex].
Providing the answer in the required format,
[tex]\[ x = -1, \frac{1}{6} \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.